Success rate of epidural labor analgesia service at a tertiary care hospital in Nepal : An observational study - Pradhan, Kripa; Bhattarai, Prajjwal Raj; Adhikari, Hemant; Sharma, Apurb (Nepal Mediciti Medical Journal, 2024)
BACKGROUND Pain experienced during childbirth is one of the most intense forms of pain that many women encounter during their lifetime. Epidural Labor Analgesia (ELA) is widely embraced as an effective technique for pain management during childbirth. The Department of Anesthesiology at Nepal Mediciti has been providing ELA service since November 2017. We conducted this study for ELA services in our institute from 1st January to 31st December 2022 to find out the success rate of the present ELA service at Nepal Mediciti. METHOD This observational study was conducted at Nepal Mediciti by reviewing data for Epidural Labor Analgesia from 1st January to 31st December 2022. RESULT In the year 2022, total deliveries at Nepal Mediciti were 886 of which normal deliveries were 193 (21.78%), and delivery via Cesarean Section was 693(78.22%). A total of 105 (54.40%) epidurals were inserted in the labor suit, of which 94 parturients had a normal delivery and 11 had Cesarean Section. CONCLUSION In our study, we found the success rate of normal delivery with ELA at Nepal Mediciti was 97.9%. The acceptance rate of ELA was 41.2%.